Financial auditing benefits: Perspective of the SME in Celaya, Guanajuato - Lozano Montero, Eva; Godínez López, Roberto; Albor Guzmán, Saúl Manuel (Acta Universitaria, 2020)
Financial auditing has been considered a reliability tool in resource management, although it has generated distrust due to its shortcomings. The objective of this research is to analyze the perception of Small and Medium Enterprise (SME) regarding the benefits generated by financial auditing as a tool for competitiveness. Using an interpretative and transversal method, some factors were identified such as the existence of a relationship between the conceptualization of auditing and the fear of its applicability, as well as a tendency to confuse the term financial audit with fiscal audit. Results suggest that when the SME are aware about the benefits of financial audit and its differences with fiscal audit, they value it and are more willing to voluntarily obtain substantial benefits that contribute to business management. In addition, the company owner’s academic studies and the age of the organization significantly influence in the willingness to have a financial audit.